260 MiR-326 promotes renal injury in murine lupus nephritis. (April 2019) - Xia, Yuan; Fang, Xuan; Xiang, Nan; Dai, Xiaojuan; Jin, Li; Li, Xiaomei; Tao, Jinhui; Li, Xiangpei
Abstract : Background: MicroRNAs play vital role in the immunopathogenesis of human and experimental lupus nephritis, but the contributions of miR-326 to renal injury in systemic lupus erythematosus (SLE) remain to be demonstrated. Here we characterize the function of the miR-326 in MRL/lpr mice of lupus nephritis. Methods: We generated MRL/lpr mice overexpression or silence in miR-326 and analyzed the clinical course of the nephritis with respect to albuminuria. In addition, renal Th17/Treg cells and IL-17A/TGF- expression were detected by flow cytometry and immune-histochemistry respectively. Results: miR-326 overexpression did increase the development of albuminuria in MRL/lpr mice. In contrast, miR-326 silence decreased the development of albuminuria. The characterization of renal CD4 +T cells in miR-326 overexpression mice revealed high numbers of infiltrating Th17 cells and low numbers of infiltrating Tregs. IL-17A and TGF- expression respectively increased and decreased in miR-326 overexpression mice. Conclusions: miR-326 overexpression plays major role in the immunopathogenesis of lupus nephritis in MRL/lpr mice. Thus, our results suggest that miR-326 may be an intriguing new therapeutic approach for patients with lupus nephritis. Funding Source(s): the National Natural Science Foundation of China 81373186